Medicinal plants: past and present use in several communities from the North-eastern Portugal - Carvalho, Ana Maria (2008)
Medicinal plants, past and present related uses emerged from broader studies conducted during several years inside 36 rural communities in Trás-os-Montes. This region, as other areas in the interior of Portugal, has seen socio-economic transformations since the 1960s that have altered landscape management and plant use. The surveys aimed to report traditional plant knowledge and uses (TK). In addition focused on the system of local knowledge on plant resources and prevalent traditional plant use and practices. Ethnographic methodology was used and consented structured enthobotanical interviews were carried out.